2022
DOI: 10.1038/s41598-022-14541-y
|View full text |Cite
|
Sign up to set email alerts
|

Random walk diffusion simulations in semi-permeable layered media with varying diffusivity

Abstract: In this paper we present random walk based solutions to diffusion in semi-permeable layered media with varying diffusivity. We propose a novel transit model for solving the interaction of random walkers with a membrane. This hybrid model is based on treating the membrane permeability and the step change in diffusion coefficient as two interactions separated by an infinitesimally small layer. By conducting an extensive analytical flux analysis, the performance of our hybrid model is compared with a commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Furthermore, we observed that MD increased, and FA decreased, with mean frequency of the power spectrum of q ( t ), demonstrating clear diffusion time effects in contrast to the in vivo data. This difference may appear due to the longer diffusion times used at the clinical scanner (a consequence of the relatively low gradient system performance in human MRI systems) and may be indicative of a higher permeability in myocardium compared with the plastic used in the phantom 64,65 . Here, we were limited by the size of the phantom; therefore, a preclinical scanner with high gradient performance was used.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that MD increased, and FA decreased, with mean frequency of the power spectrum of q ( t ), demonstrating clear diffusion time effects in contrast to the in vivo data. This difference may appear due to the longer diffusion times used at the clinical scanner (a consequence of the relatively low gradient system performance in human MRI systems) and may be indicative of a higher permeability in myocardium compared with the plastic used in the phantom 64,65 . Here, we were limited by the size of the phantom; therefore, a preclinical scanner with high gradient performance was used.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Whenever a particle interacts with a cell membrane, a probability of transit p t is computed via a transit model that represents the permeability embedded in the membrane boundary condition. 19,20 This transit model, that we refer to as the hybrid model, 20 treats the membrane permeability and the step change in diffusion as successive barrier interactions. Doing so reduces the complexity of the transit probabilities to…”
Section: Permeabilitymentioning
confidence: 99%
“…The aim of this work is to study the sensitivity of DT‐CMR parameters to changes in cell membrane permeability and microvascular perfusion. The simulations of the diffusion process use a new permeability model 20 that improves upon the treatment of the interface boundary condition 19 between regions of different diffusivity as compared to previous numerical simulations of diffusion tensor imaging. In a similar manner, the microvascular perfusion signal has been modeled assuming that a group of particles travel at constant velocities through a capillary network anisotropically oriented according to a Dimroth–Watson distribution 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Using the existing machinery of surplus risk theory and ruin analysis, we can then derive close upper bounds and explicit tight estimates for radiative metrics. Although random walk and Lévy processes have been extensively used for modeling diffuse processes [105]- [109] in various transport problems and porous media modeling, there are two shortcomings: (i) relevance to radiation heat transfer is scarce, as opposed to other problems such as probe diffusion and permeability modeling [110]- [113], (ii) closed-form derivations that lead to tangible variance reduction in MCRT are missing. The particular angle of surplus risk theory provides a richer apparatus to derive directly related quantities.…”
Section: Introductionmentioning
confidence: 99%